Implications of Childless Families in the Qur'an - Anggun, Anggun; Bunyamin, Bunyamin; Kallang, Abdul; Suhra, Sarifa; Rasyid, Idris; Kaddas, Badruddin (Lembaga Sembilan Tiga Community, 2024)
This paper examines the implications of childless families in the view of the Qur'an. This type of research uses library research, namely activities to find and collect information related to the Qur'anic view of the childfree phenomenon in marriage, using written materials such as books, documents, journal articles, previous research results, and other scientific works related to the topic of the problem. The results show that childless families in the view of the Qur'an can lead to the emergence of various negative impacts that will be experienced by families if there is no birth of children in the family. These negative impacts include; the loss of heart conditioning, the loss of blessings from a child for his parents, life will feel empty, and not including a complete family. Parents should know the nature and privilege of children in the family because it can be a side of luck for parents and their families. To avoid the negative impacts of childfree families, every married couple needs to consider a number of these negative impacts so that they can change their stance from a pro-childfree family to a family that wants offspring because children are very useful for a family.